2015
DOI: 10.1155/2015/450351
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against C1q Are a Valuable Serological Marker for Identification of Systemic Lupus Erythematosus Patients with Active Lupus Nephritis

Abstract: Objective. An early diagnosis of lupus nephritis (LN) has an important clinical implication in guiding treatments of systemic lupus erythematosus (SLE) in clinical settings. In this study, the diagnostic values of circulating autoantibodies to C1q alone or in combination with other markers for accessing active SLE and LN were evaluated. Methods. The diagnostic value of anti-C1q autoantibodies for identification of patients with active SLE disease and LN was evaluated by analyzing the level of anti-C1q antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
22
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 53 publications
11
22
1
2
Order By: Relevance
“…These data indicated that the evaluation of the simultaneous existence of antibodies against dsDNA and C1q could be useful as diagnostic and predictive biomarkers for SLE patients with kidney involvement. Several studies are consistent with our ndings [5,12,18,20]. Recently, it has been demonstrated that any de ciency in complement activation through classic and alternative pathways strongly correlated with the progression and severity of LN.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data indicated that the evaluation of the simultaneous existence of antibodies against dsDNA and C1q could be useful as diagnostic and predictive biomarkers for SLE patients with kidney involvement. Several studies are consistent with our ndings [5,12,18,20]. Recently, it has been demonstrated that any de ciency in complement activation through classic and alternative pathways strongly correlated with the progression and severity of LN.…”
Section: Discussionsupporting
confidence: 92%
“…The actual prevalence of antibodies against C1q molecules is controversial in different kidney involvements of patients with SLE. Several studies have addressed antibodies against C1q as a potential biomarker for the prediction of kidney involvement [18][19][20]. However, few investigations revealed the positive serum for anti-C1q directly correlated with only SLE disease activity and it is not speci c for kidney involvement (LN) [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…This observation supports, but does not confirm, reports that relate high αC1q ab levels to renal symptoms and/or renal flares [18]. There have been many studies over the past two decades of αC1q ab levels in disease, including SLE [17,18]. These, together with this report, suggest that quantitation and standardization of anti-C1q antibodies has a useful role in the classification of subtypes of SLE and as a potential confirmatory diagnostic and monitoring assay [17,18].…”
Section: Discussioncontrasting
confidence: 78%
“…A strong association between αC1q ab and active renal disease has been demonstrated [18]. Only nine studies have longitudinal data permitting this specific assessment (including 10,14), although other reports have supported its potential for this use [9,10,12,17]. The present study measured the levels of αC1q ab in a cohort of diagnosed and treated Western Australian SLE patients using a commercial ELISA kit.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation